Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1007/s10658-006-9093-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of host-pathogen interactions in the Pyrenophora teres f. teres (net form) – barley (Hordeum vulgare) pathosystem

Abstract: The genetics of host-pathogen interactions in the Hordeum vulgare -P. teres f. teres pathosystem was studied in twelve resistant barley accessions, i.e. CI

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 19 publications
1
20
0
1
Order By: Relevance
“…The virulence of mating progeny populations was studied on selected barley genotypes from a barley differential set previously used (Robinson & Jalli, 1996;, 2000. Barley genotypes CI 5791, CI 5822 and Manchuria carry 1-3 net blotch resistance genes (Steffenson & Webster, 1992;Afanasenko et al, 2007), Pohto has quantitative resistance and Arve is a susceptible variety (Robinson & Jalli, 1999). The resistant reaction of barley genotypes to the parental net form isolates was similar to previous studies (Robinson & Jalli, 1996).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The virulence of mating progeny populations was studied on selected barley genotypes from a barley differential set previously used (Robinson & Jalli, 1996;, 2000. Barley genotypes CI 5791, CI 5822 and Manchuria carry 1-3 net blotch resistance genes (Steffenson & Webster, 1992;Afanasenko et al, 2007), Pohto has quantitative resistance and Arve is a susceptible variety (Robinson & Jalli, 1999). The resistant reaction of barley genotypes to the parental net form isolates was similar to previous studies (Robinson & Jalli, 1996).…”
Section: Discussionsupporting
confidence: 79%
“…Necrotrophic pathogens have been reported to produce host-specific toxins (HST) that may function as effectors in inducing toxicity and disease in the host species following a gene-for-gene model (Friesen et al, 2008). There is strong evidence for a gene-for-gene interaction in the P. teres-barley pathosystem (Afanasenko et al, 2007). Lai et al (2007) identified three major avirulence genes in P. teres f. teres involved in avirulence/virulence of the fungus: AvrHar, AvrPra1 and AvrPra2, and Beattie et al (2007) identified six amplified fragment length polymorphism (AFLP) markers linked to a P. teres f. teres avirulence gene AvrHeartland.…”
Section: Introductionmentioning
confidence: 99%
“…This result agrees well with previous reports on NFNB where one to three major genes, in addition to minor genes, have been shown to control NFNB resistance/susceptibility in barley in any given biparental population (reviewed in Liu et al ., ). Current and previous genetic studies using fungal mapping populations have also shown that a few major genes in each P. teres f. teres isolate condition virulence/avirulence towards a particular host genotype (Afanasenko et al ., ; Beattie et al ., ; Lai et al ., ; Shjerve et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, Canadian Lake Shore CI2750, Tifang CI4407-1, Manchurian M-CI2330, Manchurian CI5791, Manchurian CI1251, Harbin CI4929, CIho4922, CIho5822, Atlas CI4118, Rojo CI5401, Coast CI2235, and Ming CI4797 haven been reported and used as the International Differential set previously (Afanasenko et al 2007;Afanasenko et al 2009). Seed of the international differential set was obtained from Genetic Resource Unit of ICARDA.…”
Section: Plant Materialsmentioning
confidence: 99%